Loss‐of‐Function Mutations in KIF15 Underlying a Braddock–Carey Genocopy. Issue 5 (10th March 2017) - Sleiman, Patrick M.A.; March, Michael; Nguyen, Kenny; Tian, Lifeng; Pellegrino, Renata; Hou, Cuiping; Dridi, Walid; Sager, Mohamed; Housawi, Yousef H.; Hakonarson, Hakon
Abstract : Braddock‐Carey Syndrome (BCS) is characterized by microcephaly, congenital thrombocytopenia the Pierre‐Robin sequence (PRS) and agenesis of the corpus callosum. BCS has been shown to be caused by a 21q22.11 microdeletion that encompasses multiple genes. Here we report a BCS genocopy characterized by congenital thrombocytopenia and PRS that is caused by a loss of function mutation in KIF15 in a consanguineous Saudi Arabian family. To our knowledge KIF15 is the first kinesin to the first to be associated with congenital thrombocytopenia. ABSTRACT: Braddock–Carey Syndrome (BCS) is characterized by microcephaly, congenital thrombocytopenia, Pierre–Robin sequence (PRS), and agenesis of the corpus callosum. BCS has been shown to be caused by a 21q22.11 microdeletion that encompasses multiple genes. Here, we report a BCS genocopy characterized by congenital thrombocytopenia and PRS that is caused by a loss‐of‐function mutation in KIF15 in a consanguineous Saudi Arabian family. Mutations of mitotic kinesins are a well‐established cause of microcephaly. To our knowledge, KIF15 is the first kinesin to be associated with congenital thrombocytopenia.